Respon Tanaman Aren Genjah (Arenga pinnata) dan Tanaman Kakao (Theobroma cacao L.) pada Pemberian Pupuk dengan Penanaman Sistem Jalur: RESPONSE OF AREN GENJAH (Arenga pinnata) Merr.) AND COCOA (Theobroma cacao L.) PLANTS TO FERTILIZER WITH ALLAY CROPPING LINE SYSTEM - Purwati Purwati; Yetti Elidar (Agrifarm : Jurnal Ilmu Pertanian, 2022)
Cultivation of aren genjah and cocoa with allay cropping system is a cultivation technique aimed at soil conservation and micro environment. Cultivation of plants in the field needs to get the supply of nutrients with fertilization as an effort to increase crop productivity. This study aimed to find out the response to the growth of aren genjah and cocoa plant on the application of NPK Phonska fertilizer and goat manure fertilizer with allay cropping system. The research was conducted in Badak Mekar Village Muara Badak Sub-district of Kutai Kartanegara Regency, East Kalimantan in 2016. The research method used Randomized Block Design (RAK) and repeated 4 times. The factorial experiment includes 2 factors, the first factor is NPK Phonska (N) fertilizer consisting of 3 levels: n0 = 0 kg plant-1 (control); n1 = 0.25 kg plant-1; n2 = 0.5 kg plant-1 and the second factor is goat manure fertilizer (k) consisting of 3 levels: k0 = 0 kg plant-1 (control); k1 = 2.5 kg plant-1; k2 = 5 kg plant-1. The study consisted of 9 treatments and repeated 4 times. Parameters observed: plant height increase, diameter increase and number of midrib/leaf increase. Data were analyzed by variance and if there was a real effect it would be continued with the smallest real difference test at 5% level. The results showed that NPK Phonska fertilizer very significantly on the parameters of plant heightincrease of aren genjahand cocoa plants. The treatment of NPK Phonska fertilizer at a dosage of 0.5 kg plant-1 (n2) gives the best of plant heightincrease aren genjah and cacao.